Association of rs235768 A>T polymorphism of the bone morphogenetic protein 2 gene on non-syndromic orofacial cleft in an Indonesian population - Kiranahayu, Rarasih; Suhartono, Antonius Winoto; Sulistyani, Lilies Dwi; Latief, Benny Sjariefsjah; Auerkari, Elza Ibrahim (Universitas Padjadjaran, 2020)
Introduction: Orofacial cleft is one of the many congenital malformations that often occur in human, leaving it at the fourth level of the most common orofacial birth defect findings. The incident rate is one in 700-1000 deliveries, where without therapeutic and surgical interventions, children with an orofacial cleft may have problems with speech, nutrition intake, and growth. Bone morphogenetic protein 2 (BMP-2) gene play essential roles in the migration and proliferation of neural crest cell of the early head formation and regulate mineralised tissues such as maxillary, mandible, palate and teeth. This study was aimed to analyse the BMP-2 polymorphism and its potential association with orofacial cleft in an Indonesian population. Methods: Cross-sectional study was conducted towards 128 samples, 32 samples of orofacial cleft patients and 96 samples of control. Extracted genotype and allele was determined with PCR-RFLP method using stored DNA samples from 32 orofacial cleft patients, and 96 healthy control. Results: The TT genotype was showing the p-value = 0.001, OR = 2.43% in orofacial samples (71.4%), which was significantly higher than in control groups (28.6%). The allele distribution was also considered statistically significant (p = 0.036, OR =1.89%. Conclusion: There is a significant association of rs235768 A>T polymorphism of the BMP-2 gene on non-syndromic orofacial cleft patients in Indonesia.